Standards-Based Reform and Rural School Improvement: Finding the Middle Ground - Patricia J. Kannapel (Journal of Research in Rural Education, 2000)
Two movements in school improvement are compared and contrasted: standards-based reform and rural school improvement efforts that emphasize locally-responsive, place-based curricula. While the two movements differ in philosophicalorientation, they share the following goals: increasing equity in schools, making curricula and pedagogy intellectually rigorous, and creating content and opportunity-to-learn standards. They differ in that the standards-based movement advocates the development ofstate and national standards tied to a testing and accountability program, while rural school improvement advocates believe that all standards should be developed locally and that student assessment should be designed to provide instructional feedback to teachers. The author proposes that advocates of the two approaches to school improvement work together to create a school reform movement that will lead to better schools and communities than either movement can create on its own.